School Social Work with the Use of Arts in the Context of a Participatory Action Research: Enhancing a Roma Student’s Educational Inclusion during COVID-19 - Styliani Farmaki; Konstantinos Kaplanis; Agapi Kandylaki (International Journal of School Social Work, 2025)
This article presents an arts-based systemic school social work intervention that contributed to the educational inclusion of a primary school Roma student who exhibited unstable school attendance and was excluded from tele-education during COVID-19. The intervention was part of a Participatory Action Research (PAR) project conducted by the researcher (first author) in collaboration with 13 School Social Workers (SSWs) from Greece and Cyprus. After performing an original video-song entitled “We’ve not forgotten you”, the SSWs used it as a tool in arts-based, tailor-made interventions with socially isolated and marginalized students and members of their systems (parents, classmates, teachers) to help enhance their educational inclusion. One of these interventions is presented here. It was initiated by the SSW (second author) during quarantine and evolved within the school after its reopening, utilizing collective story-writing, theatre “from within the school community”, songwriting, drawing, and craft making. The intervention contributed to the target student’s empowerment, equal participation in peer and class groups, regular school attendance and sense of belonging, along with improving his family’s relationship with other student families and the school. It also promoted interdisciplinary and inter-school collaboration and fostered a climate of inclusion and resilience in the school community during the pandemic, opening up prospects for ongoing change towards inclusion in the future.
Keywords: School Social Work; Participatory Action Research (PAR); Arts-based Systemic Intervention; Roma Student; Educational Inclusion; COVID-19